Spontaneous Intestinal Perforation in a Very Low Birth Weight Infant: Successful Management by Peritoneal Needle Suction - Chioukh, Fatma Zohra; Ben Ameur, Karim; Laamiri, Rachida; Ben Hamida, Hayet; Nouri, Abellatif; Monastiri, Kamel (Journal of Neonatal Surgery, 2016)
Please see fulltext